Power and architecture: the construction of capitals and the politics of space - Minkenberg, Michael (Space and place, 2014)
Capital cities have been the seat of political power and central stage for their state's political conflicts and rituals throughout the ages. In the modern era, they provide symbols for and confer meaning to the state, thereby contributing to the ""invention"" of the nation. Capitals capture the imagination of natives, visitors and outsiders alike, yet also express the outcomes of power struggles within the political systems in which they operate. This volume addresses the reciprocal relationships between identity, regime formation, urban planning, and public architecture in the Western world
Literaturangaben
Keywords: Aufsatzsammlung; Politische Identität; Repräsentation; Macht; Architektur; Stadtplanung; Hauptstadt